Introduction to accounting for hotels : a study guide - Vicente, Ma. Violeta V. (Mandaluyong City, Philippines : Mutual Books, Inc., 2005)
The course is intended to equip students with adequate knowledge of basic accounting principles and procedures to be able to do simple bookkeeping processes to help them understand how the reports come about and eventually to prepare them for employments in the hotel accounting offices.
UNIT 1. Introduction to accounting -- 2. Accounting theories, assumptions and procedures -- 3. Accounting for EL Grande Inn, Inc. -- 4. Recording and posting for El Grande Inn, Inc., -- 5. Financial statements of EL Grande Inn, Inc., -- 6. Analyzing EL Grande Inn, Inc's Financial statements.
Includes bibliographical references.
Keywords: HOTELS -- ACCOUNTING